AGENCY, ALTERITY, APPROPRIATION: POSTCLASSIC LOWLAND MAYA USES AND MODIFICATIONS OF THE "MIXTECA-PUEBLA" OR "INTERNATIONAL" STYLE. Issue 2 (28th November 2016) - Jordan, Keith
Abstract: Maya participation in the Postclassic Mixteca-Puebla or International Style has long been recognized in murals and manuscript painting. Recent explanations for Maya adoptions/modifications of this central Mexican style have shifted from invasion or "influence" to emphasize the active and selective participation of the Maya. I examine two examples, the solar murals of Mayapan and Flores Stela 4, to elucidate how they reflect Maya uses of the Mexican Other in service of local political and religious power. I argue that these works represent a Late Postclassic continuation of a long Maya tradition of using central Mexican forms and iconography as exotic ideological "prestige goods" reinforcing the legitimacy of local elites. They cannot be understood apart from the previous history of interactions between the Maya and central Mexico, particularly in the Early Postclassic, and some of the "Mexican" elements in these examples may derive from Maya-Mexican interactions during this earlier time. For Eloise Quiñones Keber, and in memory of H.B. Nicholson